Biogenesis, Turnover, and Mode of Action of Plant MicroRNAs([OPEN]) - Rogers, Kestrel (American Society of Plant Biologists, 2013)
MicroRNAs (miRNAs) are small RNAs that control gene expression through silencing of target mRNAs. Mature miRNAs are processed from primary miRNA transcripts by the endonuclease activity of the DICER-LIKE1 (DCL1) protein complex. Mechanisms exist that allow the DCL1 complex to precisely excise the miRNA from its precursor. Our understanding of miRNA biogenesis, particularly its intersection with transcription and other aspects of RNA metabolism such as splicing, is still evolving. Mature miRNAs are incorporated into an ARGONAUTE (AGO) effector complex competent for target gene silencing but are also subjected to turnover through a degradation mechanism that is beginning to be understood. The mechanisms of miRNA target silencing in plants are no longer limited to AGO-catalyzed slicing, and the contribution of translational inhibition is increasingly appreciated. Here, we review the mechanisms underlying the biogenesis, turnover, and activities of plant miRNAs.